Geoadditive survival models: a supplement - Andrea Hennerfeind; Andreas Brezger; Ludwig Fahrmeir (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2005)
This technical report supplements the paper Geoadditive Survival Models (Hennerfeind, Brezger and Fahrmeir, 2005, Revised for JASA). In particular, we describe the simulation study of this paper in greater detail, present additional results for the application, and provide a complete proof of Theorem 1, Corollary 1, as well as the lemmata and corollaries in the appendix.
urn:nbn:de:bvb:19-epub-1823-6
Keywords: 519